Evaluasi Pelaksanaan Sistem e-rapor pada SMA Negeri di Kota Singaraja - L.H.K Dewi; I.G.K.A Sunu; I.N. Natajaya (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to investigate both partially and simultaneously the components of context, input, process, product and the obstacles that occurred in the implementation of the E-report system at public high schools in the city of Singaraja. The CIPP model is used in this research. The population of this study was 200 teachers from three public high schools in Singaraja namely teachers of SMAN 1 Singaraja, SMAN 2 Singaraja, and SMAN 3 Singaraja with a total sample of 172 teachers. The data for each variable were collected by using the Five-point Likert scale questionnaire model with descriptive quantitative data analysis method. In order to determine the effectiveness of the E-report system implementation, the raw score is transformed into Z-score and into T-score continued to the verification of the score into the Glickman quadrant. The data analysis results show: 1) The effectiveness of the E-report system implementation from the context component is identified as effective (+), 2) The effectiveness of the E-report system implementation from the input component is identified as effective (+), 3) The effectiveness of the E-report system implementation from the process component is identified as effective (+), 4) The effectiveness of the E-report system implementation from the product component is identified as effective (+), The evaluation result on the effectiveness of the E-report system implementation from the context, input, process, product components simultaneously is identified as highly effective (+ + + +). Alternative solutions for the obstacles encountered in the implementation of the E-report system have been explored namely the solutions regarding the issue with the program coordinator contract status, organizational structure, teachers’ incompetence, students’ responses, low budget, and the socialization of the E-report program guidelines. Key words: E-report system; Evaluation Study; CIPP